A Bibliometric Analysis of Cirrhosis Nursing Research on Web of Science. (May 2020) - Guo, Lizhen; Lu, Gendi; Tian, Jun
Abstract : The aims and objectives of this study were to (1) analyze the bibliometric characteristics of articles on Web of Science from 1986 to the present using literature mining and information visualization technologies developed by CiteSpace software, (2) reflect the current situation in this field as far as possible, and (3) provide evidence for improving research on nursing and clinical liver cirrhosis in Mainland China. No bibliometric analysis exists on Web of Science regarding cirrhosis nursing research. The status of current research, including hotspots and trends, has been assessed in this study through a bibliometric analysis. Literature related to cirrhosis and nursing was identified via Web of Science. Data were then analyzed using CiteSpace software. From 1986 to 2018, a total of 179 articles were published in 109 journals by 830 researchers in 36 countries/regions. The terms "cirrhosis, " "management, " and "quality of life" emerged most frequently and indicated the hotspots in liver cirrhosis nursing literature. Among all countries/regions, the United States contributed the most research overall; Asia also played an important role in the field of liver cirrhosis nursing research. The journal Gastroenterology Nursing published the greatest number of articles. Liver cirrhosis nursing research has attracted increasing amounts of attention around the world, although it remains less robust than other fields. Cirrhosis nursing research is still in its infancy in Mainland China, and there is an urgent need for additional support from government or research institutions to improve this research focus and promote international acceptance of the research outcomes.